Pemanfaatan Sampah Sedotan Plastik dan Botol Bekas Sebagai Hiasan Sekolah (Kreativitas Hijau) - Riyanti, Riyanti; Ismiasih, Ismiasih (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Increasing environmental awareness among students is an urgent matter considering their low awareness and skills in caring for the surrounding environment. This empowerment aims to explore the use of plastic straws and used bottles as school decoration materials at SD Tunas Sejahtera Kawi Estate. The methods used are socialization, counseling and training to develop critical, creative and social skills in children. The results of this activity showed that the participants were very enthusiastic and actively participated in this empowerment. They are able to have the knowledge and skills gained after participating in activities. Apart from that, this activity is also able to increase students' awareness of the environment. This activity provides evidence that a creative approach to waste management can be effective in educating and empowering students to protect the environment.